The cult of the nation in France : inventing nationalism, 1680-1800 - Bell, David A. (David Avrom) (ACLS Fellows' publications., 2003)
In a work of lucid prose and striking originality, Bell offers the first comprehensive survey of patriotism and national sentiment in early modern France, and shows how the dialectical relationship between nationalism and religion left a complex legacy that still resonates in debates over French national identity today.